1987
DOI: 10.1149/1.2100237
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Ion Etching of Through‐the‐Wafer via Connections for Contacts to GaAs FET's

Abstract: Through‐the‐wafer via connections can provide low impedance contacts for normalGaAs FET's which significantly improve device characteristics. In this paper, we describe the use of a simple, thick, positive resist mask together with reactive ion etching in low pressure SiCl4/Cl2 mixtures. This process provides controlled via profiles suitable for connections through 100 μm thick substrates. The use of this process in the fabrication of a monolithic distributed amplifier resulted in a significant improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Cooper et al 14 also reported the effect of dc bias on the etch characteristics. The etch rate increased with increase in dc bias ͑corresponding to increase in power and ion energy͒ initially and then decreased because the high energy reactive ions may sputter off the adsorbed reactants from the surface before completion of the reaction thereby reducing etch rate.…”
Section: G570mentioning
confidence: 98%
See 3 more Smart Citations
“…Cooper et al 14 also reported the effect of dc bias on the etch characteristics. The etch rate increased with increase in dc bias ͑corresponding to increase in power and ion energy͒ initially and then decreased because the high energy reactive ions may sputter off the adsorbed reactants from the surface before completion of the reaction thereby reducing etch rate.…”
Section: G570mentioning
confidence: 98%
“…Another significant advantage of via hole grounding is that the via inductance can be predetermined, 13 increasing the reproducibility of the device performance. When via holes are used as grounding structures, gain of an amplifier improves by 2 dB or more at small signal levels 5,14 compared to the gain of the same amplifier with only ribbon wire bonding. Performance of large high power devices also makes marked improvements due to reduced thermal effects 15,16 as the via holes provide additional heat sinking.…”
Section: Via Holementioning
confidence: 99%
See 2 more Smart Citations
“…Some of these applications have been realized to some degree of success. For example, Cooper III et al (2) have successfully etched via holes for contacts to GaAs FETs, Coldren et al (3) and Vawter et al (4) have etched mirror facets for GaInAsP/InP and GaAs/A1GaAs lasers, respectively, and separation of InGaAsP/InP light emitting diodes has been demonstrated by Burton et al (5). In order for these technological needs to continue to be met in a reproducible and reliable manner, a better understanding of the complex chemical and physical mechanisms involved in the RIE process must be obtained.…”
mentioning
confidence: 99%